Preparation method of titanium / titanium alloy wire with double-gradient structure
By adopting a double-gradient structure in the titanium/titanium alloy wire, the strain and grain size structure with increasing radial gradients are formed, and the problem of plastic deterioration caused by strengthening of titanium/titanium alloy wire in the prior art is solved, and high strength and good plastic matching of the material are achieved.
Patent Information
- Application Number
- CN202411672298.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-11-21
AI Technical Summary
While increasing the strength, existing titanium/titanium alloy wires usually lead to deterioration of the plasticity of the material, and it is impossible to obtain materials with good strong plasticity matching.
The preparation method of a double-gradient structure is adopted to form the <0001> basal surface texture and ultrafine sub-grains through large strain drawing and medium-low temperature heat treatment. Combined with large strain torsion and medium-temperature heat treatment, a strain and grain size structure with increasing gradient along the radial direction is obtained.
It has achieved significant improvement in the strength and work hardening ability of titanium/titanium alloy wire while maintaining good plasticity, and overcomes the problem of material plasticity deterioration caused by strengthening means in the prior art.
Smart Images

Figure CN119710509A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a titanium / titanium alloy wire with a double gradient structure. Background Art
[0002] Titanium and titanium alloy wires are widely used in important fields such as aerospace, shipbuilding, biomedicine, and chemical industry due to their advantages of low density, high specific strength, and good corrosion resistance. With the continuous expansion of the application fields of titanium and titanium alloys, the demand and requirements for high-strength titanium and titanium alloy wires are constantly increasing.
[0003] At present, the commonly used methods for improving the strength of titanium / titanium alloy wires mainly include: (1) using alloying methods to adjust and optimize the element content ratio by adding elements such as Mo, Cr, V, Ta, Mn, Fe, and Al; using solid solution and aging treatment processes to regulate the state of the titanium / titanium alloy structure, change the content, morphology, size, distribution, etc. of different phases in the structure, produce second phase strengthening, and thus improve the strength of titanium / titanium alloy. (2) using hot deformation or cold deformation, using work hardening to improve the strength of titanium / titanium alloy. Although the above methods can improve the strength of titanium / titanium alloy wires, they usually lead to the deterioration of the plasticity of the material, and thus it is impossible to obtain titanium / titanium alloy wires with good strength-plasticity matching. Summary of the invention
[0004] Purpose of the invention: The purpose of the present invention is to provide a method for preparing a titanium / titanium alloy wire with a dual gradient structure, which can obtain a titanium / titanium alloy wire with a dual gradient heterogeneous structure. The titanium / titanium alloy wire can further improve the material strength while maintaining good plasticity, so that it has a good strength-plasticity match.
[0005] Technical solution: The method for preparing titanium / titanium alloy wire of the present invention comprises the following steps:
[0006] (1) Texture pretreatment: The titanium or titanium alloy wire is subjected to a large strain drawing with a strain of not less than 0.5. <0001> The base surface texture improves the initial strength of the wire and prepares the organization for subsequent large strain torsion;
[0007] (2) Subcrystallization pretreatment: The drawn wire is heat treated at medium and low temperatures to change the dislocation configuration, form ultrafine subgrains, and further improve the torsion performance of the wire; that is, the plasticity of the drawn wire can be restored by heat treatment at medium and low temperatures, so that it can be subjected to large strain torsion in the next step;
[0008] (3) Primary strain gradient treatment: The heat-treated wire is subjected to large strain twisting with a twisting angle of 3600° to 20000° to obtain a high-strength wire with a gradient strain increase along the radial direction (from the core to the edge); along the radial direction, the core area of the wire is soft (high plasticity) and the periphery (edge) of the wire is hard (low plasticity);
[0009] (4) Ultrafine grain gradient treatment: The twisted wire is heat treated at medium temperature to obtain a wire with ultrafine grain size decreasing gradually along the radial direction (from the core to the edge); by making the ultrafine grain size decrease gradually along the radial direction (from the core to the edge), the plasticity of the edge of the wire can be restored, so that the plasticity of the edge of the wire is balanced with the plasticity of the center area;
[0010] Affected by the residual strain, at the same temperature, the part with a larger strain has a higher recrystallization driving force and is more likely to undergo recrystallization. The part with a large recrystallization driving force will quickly form a large number of fine grains. Therefore, it is easier for the edge to form a large number of fine-grained structures than the core. And by adjusting the heat treatment temperature, a partially recrystallized structure can be prepared.
[0011] (5) Secondary strain gradient treatment: The heat-treated wire is subjected to a small strain secondary twisting with a twisting angle of 720° to 3600° to further strengthen the increasing strain gradient from the core to the edge, thereby obtaining a titanium / titanium alloy wire with a dual gradient structure.
[0012] Wherein, in step (2), the heat treatment temperature is 200°C to 400°C, and the heat treatment time is 30min to 120min.
[0013] Wherein, in step (3), the axial load of large strain torsion is 196N~343N.
[0014] Wherein, in step (4), the heat treatment temperature is 400°C to 700°C, and the heat treatment time is 10min to 120min.
[0015] Wherein, in step (2) and step (4), the heat treatment of the wire is carried out under the protection of an inert atmosphere; wherein the inert atmosphere is argon.
[0016] Wherein, in step (5), the axial load of small strain torsion is 98N to 245N.
[0017] Principle of the invention: The invention uses a large pulling force of more than 0.5 to orient the grains along the pulling direction, producing <0001> The basal texture, on the one hand, produces a texture strengthening effect and improves the initial strength of the wire. On the other hand, the basal texture and lamellar structure formed by drawing can overcome the problem of insufficient torsional performance of titanium / titanium alloy wires and make large strain torsion possible. Through low temperature pretreatment at 200℃~400℃, the dislocations generated by drawing are rearranged to form ultrafine subgrains with small size while maintaining the morphology, texture and strength of the wire lamellar organization. On the one hand, fine grain strengthening is carried out to improve the strength of the wire. On the other hand, the plasticity of the wire is restored to further improve the torsional performance of the wire. Through large strain torsion at 3600°~20000°, uneven strain is generated in the wire to obtain the The increasing strain gradient from the radial core to the edge, on the one hand, produces deformation strengthening and heterogeneous strengthening effects, significantly improving the strength of the wire, and on the other hand, prepares the strain for the subsequent grain gradient. Through the medium-temperature heat treatment at 400℃~700℃, the wire undergoes incomplete recrystallization, further refines the grain size, and makes the ultrafine grain size decrease gradually from the core to the edge along the radial direction. Through the small strain torsion of 360°~3600°, the gradually increasing strain gradient from the core to the edge is further enhanced, solving the problem of partial strength loss and strain gradient weakening after the ultrafine grain gradient treatment, and finally obtaining a heterogeneous structure with dual gradients of grain size and strain. The material has the effects of fine grain strengthening, dislocation strengthening and back stress strengthening, and has good coordinated deformation ability.
[0018] Beneficial effects: Compared with the prior art, the present invention has the following significant effects: The present invention greatly improves the strength-plasticity matching of the wire by obtaining a titanium / titanium alloy wire with a dual gradient heterogeneous structure in which both the grain size and the strain distribution present a gradient structure. The wire has both good strength and work hardening ability and good plasticity, thus overcoming the problem that the existing titanium / titanium alloy strengthening methods will lead to the deterioration of the wire's plasticity. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 is a process flow chart of the preparation method of the present invention;
[0020] Figure 2 This is a schematic diagram of tissue morphology changes corresponding to steps 3 to 5 in the method of the present invention;
[0021] Figure 3 The grain structure (a) and tensile curve (b) of the wire obtained in Example 1;
[0022] Figure 4 The grain structure (a) and tensile curve (b) of the wire obtained in Example 2;
[0023] Figure 5The grain structure (a) and tensile curve (b) of the wire obtained in Example 3;
[0024] Figure 6 The grain structure (a) and tensile curve (b) of the wire prepared in Comparative Example 1;
[0025] Figure 7 The grain structure and tensile curve of the wire prepared in Comparative Example 2. DETAILED DESCRIPTION
[0026] Example 1
[0027] like Figure 1 As shown, the method for preparing the titanium / titanium alloy wire with a dual gradient structure of the present invention comprises the following steps:
[0028] (1) TA2 wire is cold drawn with a drawing strain of 0.5;
[0029] (2) Under the protection of argon atmosphere, the cold drawn TA2 wire is heated to 400°C and kept at this temperature for 30 minutes;
[0030] (3) The pretreated TA2 wire was twisted 14000° and axially loaded with 294N;
[0031] (4) Under the protection of argon atmosphere, heat the twisted TA2 wire to 400°C and keep it at this temperature for 120 minutes;
[0032] (5) The heat-treated TA2 wire was twisted again by 720° and axially loaded with 98 N to obtain a dual-gradient TA2 wire with a grain size gradient and a strain gradient.
[0033] Figure 3 The grain structure and stress-strain curve of the dual-gradient TA2 wire obtained in this embodiment. Figure 3 (a) The metallographic microscopic image of the material shows that the grain size of TA2 prepared in Example 1 gradually decreases from the core to the edge, presenting a grain size gradient structure. Figure 3 (b) It can be seen that its yield strength is 375 MPa, tensile strength is 420 MPa, uniform elongation is 9.8%, and elongation at break is 43%; the static toughness of the material reaches 18000 MPa·%, indicating that the material of Example 1 has a good strength-plasticity match.
[0034] Example 2
[0035] The method for preparing a titanium / titanium alloy wire having a dual gradient structure of the present invention comprises the following steps:
[0036] (1) TA2 wire is cold drawn with a drawing strain of 0.8;
[0037] (2) Under the protection of argon atmosphere, the cold drawn TA2 wire is heated to 200°C and kept at this temperature for 120 minutes;
[0038] (3) The pretreated TA2 wire was twisted 7200° and axially loaded with 196N;
[0039] (4) Under the protection of argon atmosphere, heat the twisted TA2 wire to 700°C and keep it at this temperature for 10 minutes;
[0040] (5) The heat-treated TA2 wire was twisted again by 1800° and axially loaded with 196 N to obtain a dual-gradient TA2 wire with a grain size gradient and a strain gradient.
[0041] Figure 4 The grain structure and stress-strain curve of the dual-gradient TA2 wire obtained in this embodiment. Figure 4 (a) The metallographic microscopic image of the material shows that the grain size of TA2 prepared in Example 2 gradually decreases from the core to the edge, presenting a grain size gradient structure. At the same time, a small amount of broken grains were found at the edge, which are the deformed grains introduced during the twisting in step (5). Figure 4 (b) It can be seen that its yield strength is 405 MPa, tensile strength is 489 MPa, uniform elongation is 5.4%, and elongation at break is 37%; the static toughness of the material reaches 16807 MPa·%, indicating that the material of Example 2 has a good strength-plasticity match.
[0042] Example 3
[0043] The method for preparing a titanium / titanium alloy wire having a dual gradient structure of the present invention comprises the following steps:
[0044] (1) TA2 wire is cold drawn with a drawing strain of 0.6;
[0045] (2) Under the protection of argon atmosphere, the cold drawn TA2 wire is heated to 350°C and kept at this temperature for 30 minutes;
[0046] (3) The pretreated TA2 wire was twisted 20000° and axially loaded with 343N;
[0047] (4) Under the protection of argon atmosphere, heat the twisted TA2 wire to 650°C and keep it warm for 20 minutes;
[0048] (5) The heat-treated TA2 wire was twisted again by 3600° and axially loaded with 245 N to obtain a dual-gradient TA2 wire with a grain size gradient and a strain gradient.
[0049] Figure 5The grain structure and stress-strain curve of the dual-gradient TA2 wire obtained in this embodiment. Figure 5 (a) The metallographic microscopic image of the material shows that the grain size of TA2 prepared in Example 3 gradually decreases from the core to the edge, presenting a grain size gradient structure. At the same time, relatively more broken grains are found at the edge, which are deformed grains introduced during the twisting in step (5). Since the number of pre-twisting turns (first twisting) in Example 3 is greater than that in Examples 1 and 2, the grain size of the prepared material is smaller than that in Examples 1 and 2 as a whole. Figure 5 (b) It can be seen that its yield strength is 433 MPa, tensile strength is 524 MPa, uniform elongation is 4.3%, and elongation at break is 25.8%; the static toughness of the material reaches 16580 MPa·%, indicating that the material of Example 3 has a good strength-plasticity match.
[0050] Comparative Example 1
[0051] A method for preparing a titanium / titanium alloy wire comprises the following steps:
[0052] (1) TA2 wire was cold drawn with a drawing strain of 0.15;
[0053] (2) Under the protection of argon atmosphere, the cold drawn TA2 wire is heated to 400°C and kept at this temperature for 30 minutes;
[0054] (3) The pretreated TA2 wire was twisted 720° and axially loaded with 98N;
[0055] (4) Under the protection of argon atmosphere, heat the twisted TA2 wire to 400°C and keep it at this temperature for 120 minutes;
[0056] (5) The heat-treated TA2 wire was twisted again by 720° and axially loaded with 98 N to obtain the TA2 wire.
[0057] Figure 6 The grain structure and stress-strain curve of the TA2 wire prepared in Comparative Example 1. Figure 6 It can be seen that its yield strength is 267MPa, tensile strength is 376MPa, uniform elongation is 10.4%, and elongation at break is 16.3%. Since the initial strain of the TA2 wire during pretreatment is low, it is impossible to form an axial strengthening texture. At the same time, the first torsion strain is low, and the residual strain of each part of the material in the radial direction is low, resulting in partial recrystallization and grain refinement in the incomplete annealing process. It is also impossible to form a grain size gradient structure, so the strength and plasticity of the material are at a low level.
[0058] Comparative Example 2
[0059] A method for preparing a titanium / titanium alloy wire comprises the following steps:
[0060] (1) TA2 wire is cold drawn with a drawing strain of 0.5;
[0061] (2) Under the protection of argon atmosphere, the cold drawn TA2 wire is heated to 650°C and kept at this temperature for 40 minutes;
[0062] (3) The pretreated TA2 wire was twisted 2880° and axially loaded with 245 N to obtain the TA2 wire.
[0063] Figure 7 The grain structure and stress-strain curve of the TA2 wire prepared in Comparative Example 2. Figure 7 It can be seen that the yield strength of the material is 311MPa, the tensile strength is 401MPa, the uniform elongation is 10.4%, and the elongation at break is 13.3%. Since the sample has not undergone large strain torsion combined with heat treatment, no grain size gradient structure is produced. The sample was subsequently subjected to small strain torsion and finally introduced a single strain gradient structure. The introduced strain gradient does not have a large number of grain boundaries provided by fine grains to coordinate deformation. The introduced unevenly distributed strain further leads to excessive local strain during the deformation process, thereby generating cracks, resulting in a decrease in the plasticity of the material, higher strength but poorer plasticity, and thus poor strength-plasticity matching of the material.
[0064] Through Examples 1 to 3, it can be found that as the number of twisting turns (first twisting) increases, the grain size of the material after heat treatment decreases, but a gradient structure of grain size gradually decreasing from the core to the edge can still be formed. This is related to the recrystallization driving force caused by residual strain. During annealing, the area with a larger recrystallization driving force preferentially recrystallizes and quickly forms a large number of fine grains. Combining Examples 1 to 3 and Comparative Examples 1 to 2, it can be found that the dual-gradient structure material has a better coordinated deformation ability, so that the material has an excellent match of strength and plasticity. During the deformation process, the two gradient structures can interact with each other, reduce local strain, and produce dynamic strain adjustment, so that the material has better plasticity. At the same time, due to the effects of fine grain strengthening and dislocation strengthening, the material has excellent strength, and the back stress generated by the heterogeneous structure during the deformation process can also synergistically improve the strength of the material. Therefore, the titanium / titanium alloy wire prepared by the method of the present invention can significantly improve the hardness, strength and work hardening ability of the material while maintaining good plasticity.
Claims
1. A method for preparing a titanium / titanium alloy wire having a dual gradient structure, characterized in that: The steps include: (1) Texture pretreatment: The titanium / titanium alloy wire is subjected to high strain drawing with a strain of not less than 0.5; (2) Subcrystallization pretreatment: The drawn wire is heat treated at medium to low temperature; (3) Primary strain gradient treatment: The heat-treated wire is subjected to a large strain twisting at a twisting angle of 3600° to 20000° to obtain a wire whose strain increases gradually from the core to the edge along the radial direction; (4) Ultrafine grain gradient treatment: The twisted wire is heat treated at medium temperature to obtain a wire with ultrafine grain size decreasing gradually from the core to the edge along the radial direction; (5) Secondary strain gradient treatment: The heat-treated wire is subjected to a small strain twisting at a twisting angle of 720° to 3600° to obtain a titanium / titanium alloy wire with a dual gradient structure.
2. The method for preparing the titanium / titanium alloy wire according to claim 1, characterized in that: In step (1), after a large strain drawing with a strain of not less than 0.5 is performed, the grains in the wire are oriented along the drawing direction, producing <0001> Base surface texture.
3. The method for preparing the titanium / titanium alloy wire according to claim 1, characterized in that: In step (2), the heat treatment temperature is 200°C to 400°C.
4. The method for preparing the titanium / titanium alloy wire according to claim 1, characterized in that: In step (2), the heat treatment time is 30 min to 120 min.
5. The method for preparing the titanium / titanium alloy wire according to claim 1, characterized in that: In step (3), the axial load of large strain torsion is 196N to 343N.
6. The method for preparing the titanium / titanium alloy wire according to claim 1, characterized in that: In step (4), the heat treatment temperature is 400°C to 700°C.
7. The method for preparing the titanium / titanium alloy wire according to claim 1, characterized in that: In step (4), the heat treatment time is 10 min to 120 min.
8. The method for preparing titanium / titanium alloy wire according to claim 1, characterized in that: In step (2) and step (4), the heat treatment of the wire is carried out under the protection of an inert atmosphere.
9. The method for preparing a titanium / titanium alloy wire according to claim 1, characterized in that: In step (5), the axial load of small strain torsion is 98N to 245N.
10. The method for preparing titanium / titanium alloy wire according to claim 1, characterized in that: In step (5), the titanium / titanium alloy wire with a dual gradient structure is a titanium / titanium alloy wire having both an ultrafine grain size gradient and a strain gradient.
Citation Information
Patent Citations
Gradient structure aluminum alloy material and preparation method thereof
CN114411072A
Method for improving mechanical property of magnesium alloy bar
CN116274444A
Austenitic stainless steel wire with gradient nano dislocation structure and preparation method of austenitic stainless steel wire
CN117385149A
Method for preparing high-strength high-plasticity gradient structure wire
CN118268401A
Tubular torsion bar
US20130300043A1